2017
DOI: 10.1080/17429145.2017.1406999
|View full text |Cite
|
Sign up to set email alerts
|

Effect of intraspecific competition on biomass partitioning of Larix principis-rupprechtii

Abstract: It is acknowledged that trees biomass allocation in response to environmental conditions. However, it remains poorly understood what strategies of plant biomass allocation with inter-and intraspecific interactions of tree species in forest stands. Such information is important for revealing strategies of plant biomass allocation with plant competition. To address this problem, a study was conducted in Larix principis-rupprechtii plantations to evaluate the impact of plant competition on plant biomass allocatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
20
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 18 publications
3
20
1
Order By: Relevance
“…Trees compete for both light and growing space, and we found that under strong competition, Liaodong oak trees reduced the biomass of their branches to allow the biomass of the belowground parts to be increased while also giving priority to high growth of the trunk. This is different from the conclusion of Wang et al (2012) and Zhou et al (2018), they suggested that the allocation of biomass accorded to the principle of optimal biomass allocation, which was the intense light competition will promote the biomass allocation to the foliage(components that receive lights) and branches(components that support foliage). The different findings for Liaodong oak may be explained as follows.…”
Section: Discussioncontrasting
confidence: 74%
“…Trees compete for both light and growing space, and we found that under strong competition, Liaodong oak trees reduced the biomass of their branches to allow the biomass of the belowground parts to be increased while also giving priority to high growth of the trunk. This is different from the conclusion of Wang et al (2012) and Zhou et al (2018), they suggested that the allocation of biomass accorded to the principle of optimal biomass allocation, which was the intense light competition will promote the biomass allocation to the foliage(components that receive lights) and branches(components that support foliage). The different findings for Liaodong oak may be explained as follows.…”
Section: Discussioncontrasting
confidence: 74%
“…Furthermore, according to the theory of biomass allocation, high competition may increase or reduce biomass allocation in plants [63,64]. Zhou et al [33] found that the biomass ratio of roots and stems decreased with increasing intensity of competition from neighboring trees, while biomass at the level of branches and leaves increased.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown the relationship between radial growth and height growth of trees [65,66] and that the crown:height ratio may quantify competition among trees [67,68]. Therefore, the diameter and height of a tree are not only closely linked to light capture but also to the effects of water, nutrients, and soil conditions [33]. Moreover, according to the results of Zhou et al [33], during growth, plants change how they are affected by the competition of neighboring plants, and their competitive effect on other plants.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The growth dynamics of every element of tree architecture such as height, DBH, and canopy cover have long been considered as dendrometric factors that determine the intensity of competition between trees. Several previous studies have proven that DBH is an important factor that influences the intensity of competition between trees both interspecific and intraspecific competition (Gonzalez de Andres et al 2018;Zhou 2017;Da Cunha et al 2016).…”
Section: The Effect Of Competition On Merbaumentioning
confidence: 99%